Template-free and surfactant free solvothermal synthesis of mesoporous manganese oxide with enhanced activity in the oxygen evolution reaction - Lyons, Michael; Colavita, Paula; Duesberg, Georg (My University, 2017)
Porous manganese carbonate was obtained via solvothermal synthesis using ethanol and urea. The manganese carbonate was subsequently used as a precursor to synthesise mesoporous manganese oxides via thermal treatments at three various temperatures. X-ray diffraction and Extended X-ray Absorption Fine Structure (EXAFS) results shows that γ-MnO2 is synthesised at 380 and 450 °C while Mn2O3 is produced at the annealing temperature of 575 °C. X-ray absorption spectra show that γ-MnO2 converts completely to Mn2O3 after annealing over the 450-575 °C range. The oxides obtained at 380 °C and 450 °C possess extremely high specific surface area, which is of interest for catalytic applications. The oxides were investigated as electrocatalysts for the oxygen evolution reaction; the oxide prepared at the lowest annealing temperature was found to be the optimum catalyst with an overpotential of 427 ± 10 mV at a current density of 10 mA cm-2, normalised by the geometric area. The improved catalytic activity was related to the presence of defect-rich and highly porous manganese dioxide at the lowest annealing temperature.
PUBLISHED
Keywords: electrocatalysts; Porous manganese carbonate; solvothermal synthesis; Nanoscience & Materials; Hydrogen; OXIDE SURFACES